Effectiveness of Regional Education Expenditure Management in a Remote Highland Yalimo Regency, Papua Mountains, Indonesia - Paul Yare; Julius Ary Mollet; Risky Novan Ngutra (Studies in Economy and Public Policy, 2026)
Purpose: This study examines the effectiveness of regional education expenditure management in Yalimo Regency, one of the most geographically isolated districts in Papua Mountains Province, Indonesia, where consecutive budget increases have coincided with only marginal gains in education quality. Methodology: A mixed methods design combined quantitative analysis of education budget realization data from 2021 to 2025, sourced from the regional financial and asset management agency of Yalimo Regency, with a phenomenological inquiry involving ten key informants, analyzed through the Colaizzi-Moustakas protocol. Results: Total education spending grew from IDR 70.8 billion in 2021 to IDR 161.3 billion in 2024 before contracting by 19.15% in 2025. Capital expenditure achieved 96.54% average effectiveness, while operational expenditure averaged only 69.94%, a 26.6 percentage point gap. Phenomenological analysis identified four inhibiting factors, geographic barriers, administrative fear syndrome, subsistence driven discount rates, and teacher welfare deficits, alongside three enabling factors, political commitment, the Special Autonomy Fund, and traditional leadership. Conclusions: Yalimo exhibits a hollow infrastructure problem in which strong capital execution coexists with chronic operational underperformance, extending displacement effect theory to structural geographic barriers and revealing a stewardship paradox in which punitive audit systems discourage execution. Limitations: The single regency scope and one fiscal cycle window restrict generalizability to other highland districts. Contributions: The study extends displacement effect and stewardship theory to fragile remote governance contexts and offers evidence based policy guidance for reforming education expenditure management in underdeveloped frontier districts across Indonesia.